Conceptual Model of Digital Payments from the SOR Perspective at Dompet Dhuafa Central Kalimantan: a Stimulus-Organism-Response Approach - Izzat Nabila, Bayuni; Noor Sayuti, Muhammad; Zulkifli, Zulkifli; Safitri, Novi Angga (Management of Zakat and Waqf Journal (MAZAWA), 2026)
Low participation in zakat payment and the persistence of conventional payment habits remain important challenges for zakat institutions, even as digital transactions become increasingly common in Indonesian society. In response to this development, Dompet Dhuafa Kalimantan Tengah has adopted digital payment channels to facilitate zakat and donation payments. This study examines how digital payment features shape zakat payment decisions through the Stimulus–Organism–Response (SOR) framework. The study employed a qualitative case-study approach. Data were collected through in-depth interviews with institutional managers and users of digital payment services, supported by field observations and institutional documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that digital payment features function as external stimuli by increasing transaction convenience, speed, accessibility, and flexibility. These stimuli are processed through users’ perceptions of ease, usefulness, security, trust in the institution, and religious assurance. At the response stage, these evaluations are reflected in the decision to pay zakat through digital channels, repeated use, and selective channel preferences. Internal documentation cited in this study also indicates that 205 donors used digital payment channels in 2025. Nevertheless, digital payment features are not the sole determinant of zakat payment decisions; institutional trust, spiritual motivation, prior experience, and digital literacy remain central factors. The study concludes that digital payment features primarily facilitate and reinforce zakat payment decisions rather than independently generate them.